Twin deficits hypothesis: new empirical evidences from West African countries (2014)
The paper investigated the existence of Granger-causality between current account and government budget balances, with and without considering the effective real exchange rate and interest rate, over the period 1970-2008, for 14 West African (WA) countries individually and along sample groupings. The analysis is conducted within the framework of granger non-causality test and Vector Autoregression (VAR) approach on both panel data for the region and country groupings, and time series data for each individual country estimates. The results confirmed the twin-deficit relationship, with a causal relation from budget deficits to current account deficits for two countries: Ghana, and Mali; inverse relationship running from current account deficit to budget deficit for another two countries: Cote D’Ivoire and Togo. Existence of bidirectional causality and Ricardian equivalent hypothesis were confirmed for (Guinea Bissau, Mauritania, Niger, Nigeria and Senegal) and (Benin, Burkina Faso, Gambia, Guinea, and Sierra Leone), respectively. The results point to the existence of two major channels through which budget deficit affects the current account deficit. The first is the direct causal link from budget deficit to current account deficit and second, is the indirect channel that runs from budget deficit to higher interest rate to appreciation of the currency, which in turn worsens the current account deficit. There are indications that fiscal tightening (budget cuts) tends to correct the current account deficit directly as well as indirectly through interest and exchange rates.